Market Level Price Analysis of Copra Trading in the Philippines - Susan M. Rivera; Flordeliza A. Lantican (International Coconut Community, 2010)
The dynamics in market level prices was examined for Philippine copra trading. The analysis of the price formation process in the copra miller-dealer-farmer markets showed that a weak form of market integration characterized the trading of copra resecada between dealers and millers in all Philippine regions. In contrast, integration of any form was absent between miller-farmer and dealer-farmer in all regions except in Region V. Likewise, no integration was noted in all market levels when dealers and millers used copra resecada price while farmers were given the copra corriente Pasa price. Important factors were identified that contributed to the level of market integration. Recommendations made encompass areas on coconut production and productivity, market infrastructure and facilities, and pricing system in copra trading.